The Role of Islamic economics and Finance in Preventing Financial Crises in Conventional Financial Systems - Uluyol, Burhan; Uluyol, Burhan (My University, 2023)
*
7th International Conference on Islamic Banking & Finance (ICIBF-2023), 14-15 November 2023.